Relasi Agama dan Media Digital Transformasi Otoritas Keagamaan di Era Komunikasi Virtual - Ni Made Yuliani (Jurnal Penelitian Agama Hindu, 2026)
The transformation of religious authority has become a central issue in the era of digital communication, as religious discourse increasingly shifts from institutional spaces to virtual platforms. This study examines how digital media reshapes religious authority through virtual communication practices on YouTube, Instagram, and TikTok. Employing a qualitative descriptive-analytical approach, the research utilizes digital ethnographic observation, in-depth interviews, and documentation of online preaching content and community interactions. The findings reveal that digital media produces new configurations of religious authority that are no longer grounded solely in institutional legitimacy, but also in communicative competence, audience intimacy, and strategic engagement with social media algorithms. While digital platforms expand access to religious knowledge and encourage participatory engagement among believers, they simultaneously generate challenges related to authority fragmentation, authenticity, and the circulation of unverified religious narratives. The study theoretically implies a shift from a hierarchical model of religious authority toward a networked and relational form, in which legitimacy is continuously negotiated within digital spaces rather than formally ascribed.